2021
DOI: 10.1002/bem.22354
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field Affects Growth and Yield of Sunflower Under Different Moisture Stress Conditions

Abstract: Magnetic field treatments of seeds have shown significant effects on the enhancement of crop growth. Soil moisture stress is the major constraint in the production of the sunflower crop. Therefore, the experiment was conducted to investigate the effect of a 200 mT magnetic field for 2 h on crop growth, and yield of sunflower crops raised from magnetically treated seeds sown under different moisture stress conditions. Results showed that plants from magnetically treated seeds had higher leaf area index, shoot l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A significant number works on plants related to SMF with inductions from 4 to 500 mT [145][146][147]. Works on ELF-MF variables are not numerous.…”
Section: Effects On the Whole Organism (Laboratory Studies)mentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number works on plants related to SMF with inductions from 4 to 500 mT [145][146][147]. Works on ELF-MF variables are not numerous.…”
Section: Effects On the Whole Organism (Laboratory Studies)mentioning
confidence: 99%
“…The dependence of ELF-MF effects on time after exposure can have different characteristics. The degree of manifestation of biological effects can be either monotonically increasing/decreasing with time or have a complex form of increasing and decreasing [142,147,160,221]. In particular, it has been shown in fruit flies that the effects of magnetic exposure can be manifested in subsequent generations, F1, F2, etc.…”
Section: Influence Of Environmental Factorsmentioning
confidence: 99%
“…Helianthus annuus L. seeds exhibit low production under soil moisture stress. The application of a 200 MT magnetic field to Helianthus seeds could effectively improve crop growth and yield [20]. This suggested that magnetic field treatment not only impacted the internal physiological metabolism of seeds but also mitigated the inhibition of seed germination caused by adverse conditions.…”
Section: Introductionmentioning
confidence: 97%
“…Maffei [7] and Pietruszewski and Martinez [8] give an overview of the studies that have addressed how magnetic fields can affect plants. Several other reviews have stressed the beneficial effects on seed invigoration and seedling performance of "magneto-priming", i.e., a pre-sowing treatment of seeds with magnetic fields [9], classifying them under eustressors [10], as well as the better reaction of the plant to environmental stress [11]. This method is critical because it offers important advantages compared to chemical treatments of the seeds [12].…”
Section: Introductionmentioning
confidence: 99%